2012
DOI: 10.1088/0266-5611/28/6/065008
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of the elastography inverse problem for incompressible nonlinear planar hyperelasticity

Abstract: The uniqueness of several 2D inverse problems for incompressible nonlinear hyperelasticity is studied. These problems are motivated by elastography, in which one is given a measured deformation field in a 2D domain and seeks to reconstruct the pointwise distribution of material parameters within. Two classes of models are considered. The simpler class is material models characterized by a single material parameter exemplified by the Neo-Hookean model. The second class of material models considered is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This behavior is consistent with the uniqueness of the inversion, which may be expected from the results of [47]. …”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…This behavior is consistent with the uniqueness of the inversion, which may be expected from the results of [47]. …”
Section: Methodssupporting
confidence: 91%
“…This is because we do not impose any nonzero traction boundary condition in our boundary value problem. The nonlinear parameter γ is reconstructed uniquely if its value is specified at some location in the domain, or if a lower bound is specified [47]. We adopt the latter approach and select the lower bound to be one.…”
Section: Methodsmentioning
confidence: 99%
“…However, for a large class of hyperelastic constitutive models with two parameters it has been shown that given two deformation fields: one at small strain, and another at large strain, we are guaranteed a unique solution for the two parameters up to two undetermined constants [Ferreira et al, 2012]. These constants can be determined by knowing these parameters at one point within the domain.…”
Section: The Inverse Problemmentioning
confidence: 99%
“…2. In order to solve for both the shear modulus and the nonlinear parameter , it is necessary to measure a displacement field at small strains .jruj 1/ and another at a finite value of strain [17]. The first displacement field is then used to determine the shear modulus while fixing to a small constant (say 1) throughout the domain.…”
Section: Inverse Problemmentioning
confidence: 99%
“…In quasi-static elasticity imaging, one typically has at most a measured quasi-static displacement field. From such data, then even in the most optimistic modeling case, one can determine the shear modulus of the tissue only up to a multiplicative constant [15][16][17][18]. This is because in the equations of motion, there is no term on the right-hand-side in order to calibrate the material parameters (see Equation (1) in the following section).…”
mentioning
confidence: 99%